Continuous dynamic recrystallization in a Zn–Cu–Ti sheet subjected to bilinear tensile strain - Leonard, Martin Eduardo (2020)
Research on zinc sheet formability, relevant for its technological applications, requires deeper understanding of the microstructural features that govern the plastic response of the material. In this work, a microstructural analysis by means of electron back-scattered diffraction (EBSD) technique was conducted on a commercial Zn?Cu?Ti sheet subjected to a bilinear tensile test at room temperature and low strain rate (5 × 10−4 s−1). The refinement of the granular structure is analyzed in terms of the development of subgrains within initially large grains, which eventually evolve into high angle boundary grains. This continuous dynamic recrystallization (CDRX) mechanism appears as a key factor in order to explain the grain fragmentation process and the weakening of the texture observed during straining of this alloy.---La investigación de la conformabilidad de chapas de zinc, relevante para sus aplicaciones tecnológicas, requiere una comprensión más profunda de las características microestructurales que rigen la respuesta plástica del material. En este trabajo se realizó un análisis microestructural mediante la técnica de difracción de electrones retrodispersados (EBSD) en una chapa comercial de Zn-Cu-Ti sometida a un ensayo de tracción bilineal a temperatura ambiente y a baja velocidad de deformación. El afinamiento de la estructura granular se analiza en términos del desarrollo de subgranos dentro de granos inicialmente grandes, que eventualmente evolucionan en granos con bordes de ángulo alto. Este mecanismo de recristalización dinámica continua (CDRX) aparece como un factor clave para explicar el proceso de fragmentación sufrido por los granos y la atenuación de la textura cristalográfica observados durante la deformación de esta aleación.